"The Use of Drones: From the Perspective of Regulation and National Defense and Security" (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Aerospace technology is developing very rapidly, especially in the field of drone technology. The term drone usually refers to an unmanned aircraft, or in other words referred to an Unmanned Aerial Vehicle (UAV). Nowadays, drones can perform an impressive range of tasks, from military operations to helping human life, and as of size, drone can be as big as an airplane or even as small as the palm of your hand.  This growing use of drones requires an arrangement for their operation. It is also necessary to have clarity about the Ministries or Government Institutions given the clear authority in granting permits and supervision for drone operations so that there is no ambiguity and overlapping of authority. For this reason, regulations or statutory regulations are needed to ensure the interests of aviation safety and national defense and security. This paper will review the drone arrangements for the interest of both civilian and military purposes. The method used is mapping regulation, namely by studying the regulations related to drones and literature study for the theory and expert opinion published in books, journals, and other sources; and a resume of the results of the implementation of a focus group discussion involving experts in the field of drone technology. The existing statutory regulations to the subject of drones seems not to have accommodated the public interest as well as the interests of defense and security. Drone settings are still limited to flight safety aspects with the aim of drone flights not endangering the safety of civil aviation. The substance that needs to be considered in drone settings is that the use of drones must also consider aspects of welfare and aspects of national defense and security